2020
DOI: 10.1186/s12882-020-01937-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of protein carbonyl, a marker of oxidative stress, are associated with overhydration, sarcopenia and mortality in hemodialysis patients

Abstract: Background: Increased oxidative stress in end-stage renal disease is regarded as one of the important mechanisms in the atherosclerosis and muscle wasting. However, studies examining the clinical significance of oxidative stress by direct measurement of these markers and its association with volume status and sarcopenia are limited. Methods: A follow-up cross-sectional study was performed in stable hemodialysis (HD) patients and serum protein carbonyl levels were measured as a biomarker of oxidative stress. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…It is a big advantage that it can be repeatedly measured in bed-side non-invasively, very easily and quickly. Based on various information measured by BCM, we have previously conducted a study in dialysis patients and reported the results 11 , 14 , 40 43 . As such, this study was conducted as an extension of the study conducted on dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is a big advantage that it can be repeatedly measured in bed-side non-invasively, very easily and quickly. Based on various information measured by BCM, we have previously conducted a study in dialysis patients and reported the results 11 , 14 , 40 43 . As such, this study was conducted as an extension of the study conducted on dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The serum concentration of carbonylated proteins correlates negatively with albumin levels, an extracellular molecule known as positive acute-phase protein. Such correlation reflects the fact that a low level of serum albumin signals the presence of inflammation and oxidative stress [ 142 ]. Elevated carbonyl protein levels have been detected in multiple pathologies, such as DM [ 143 ], rheumatoid arthritis [ 144 ], chronic renal failure, or sepsis [ 145 ].…”
Section: Markers Of Oxidative Stress In Older Adults With Koamentioning
confidence: 99%
“…It is a major product of peroxynitrite attack on proteins with an addition of a nitro group to the orthoposition of tyrosine. 3-NT has been used as a biomarker of nitrative damage in vivo [ 21 ]. The presence of 3-NT was previously reported in some carcinomas [ 22 ], in ccRCC through immunohistochemically staining, in contrast nephropathy [ 23 ], as a biomarker for vascular involvement in Fabry disease [ 24 ], and in preeclampsia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%